Contrast‐enhanced nano‐CT reveals soft dental tissues and cellular layers. (3rd May 2021) - Hildebrand, T.; Nogueira, L.; Sunde, P. T.; Ørstavik, D.; Glasmacher, B.; Haugen, H. J.
Abstract: Aim: To introduce a methodology designed to simultaneously visualize dental ultrastructures, including cellular and soft tissue components, by utilizing phosphotungstic acid (PTA) as a contrast‐enhancement agent. Methodology: Sound third molars were collected from healthy human adults and fixed in 4% buffered paraformaldehyde. To evaluate the impact of PTA in concentrations of 0.3%, 0.7% and 1% on dental soft and hard tissues for CT imaging, cementum and dentine‐pulp sections were cut, dehydrated and stained with immersion periods of 12, 24 h, 2 days or 5 days. The samples were scanned in a high‐resolution nano‐CT device using pixel sizes down to 0.5 µm to examine both the cementum and pulpal regions. Results: Dental cementum and periodontium as well as odontoblasts and predentine were made visible through PTA staining in high‐resolution three‐dimensional nano‐CT scans. Different segments of the tooth required different staining protocols. The thickness of the cementum could be computed over the length of the tooth once it was made visible by the PTA‐enhanced contrast, and the attached soft tissue components of the interior of the tooth could be shown on the dentine‐pulp interface in greater detail. Three‐dimensional illustrations allowed a histology‐like visualization of the sections in all orientations with a single scan and easy sample preparation. The segmentation of the sigmoidal dentinal tubules and the surrounding dentine allowed a three‐dimensional investigation and quantitative of the dentine composition, such as the tubular lumen or the ratio of the tubular lumen area to the dentinal surface. Conclusion: The staining protocol made it possible to visualize hard tissues along with cellular layers and soft tissues in teeth using a laboratory‐based nano‐CT technique. The protocol depended on both tissue type and size. This methodology offers enhanced possibilities for the concomitant visualization of soft and hard dental tissues.